2014
DOI: 10.1104/pp.114.236901
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis NUCLEUS- AND PHRAGMOPLAST-LOCALIZED KINASE1-Related Protein Kinases Are Required for Elicitor-Induced Oxidative Burst and Immunity

Abstract: Plant immunity is activated through complex and cross-talking transduction pathways that include a mitogen-activated protein kinase phosphorylation cascade. Here, we have investigated the role in immunity of the Arabidopsis (Arabidopsis thaliana) gene subfamily that encodes the mitogen-activated protein triple kinases indicated as ARABIDOPSIS NUCLEUS-AND PHRAGMOPLAST-LOCALIZED KINASE1-RELATED PROTEIN KINASE1 (ANP1), ANP2, and ANP3. For this study, we used representative danger signals (elicitors) belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 62 publications
3
81
0
1
Order By: Relevance
“…In the Wassilewskija (WS) ecotype A. thaliana , elf26-triggered ROS production (30 min) is not reduced in both atmpk6 mutants and atmkp1/atmpk6 (WS) double mutants [53]. Recently, it has been shown that in anp2anp3 (WS) double mutants or β-estradiol-inducible anp1anp2anp3 (WS) conditional triple mutants, elf18-induced production of ROS was compromised but activation of AtMPK3/AtMPK6 was normal [151]. Collectively, these data demonstrate that, in the early stage of PTI (about the first 30 min), PAMP-activated AtMPK3/AtMPK6 may occur independent of the PAMP-triggered ROS production.…”
Section: Rboh-dependent Ros Production and Mapk Cascades In Pamp-trigmentioning
confidence: 99%
“…In the Wassilewskija (WS) ecotype A. thaliana , elf26-triggered ROS production (30 min) is not reduced in both atmpk6 mutants and atmkp1/atmpk6 (WS) double mutants [53]. Recently, it has been shown that in anp2anp3 (WS) double mutants or β-estradiol-inducible anp1anp2anp3 (WS) conditional triple mutants, elf18-induced production of ROS was compromised but activation of AtMPK3/AtMPK6 was normal [151]. Collectively, these data demonstrate that, in the early stage of PTI (about the first 30 min), PAMP-activated AtMPK3/AtMPK6 may occur independent of the PAMP-triggered ROS production.…”
Section: Rboh-dependent Ros Production and Mapk Cascades In Pamp-trigmentioning
confidence: 99%
“…8). Several studies demonstrated that resistance against B. cinerea (and other necrotrophs) is accompanied by the generation of ROS, and mutants impaired in ROS production failed to resist the necrotrophic pathogen (Contreras-Cornejo et al, 2011;Kraepiel et al, 2011;L'Haridon et al, 2011;Rasul et al, 2012;Savatin et al, 2014;Zhang et al, 2014). It has been shown that LCBs but not LCB-Ps alone are able to induce ROS production (Peer et al, 2011).…”
Section: Interconnections Between Sphingolipids and Defense Mechanismsmentioning
confidence: 99%
“…Homogalacturonan degradation gives rise to small breakage products (OGs), which form ligands that can bind to WAKs (Brutus et al, 2010). This binding activates signaling processes involving salicylic acid (SA), NO and RBOHD-derived ROS as well as signal translation via ANPs/MPK3/MPK6, which induces classic defense responses (Ferrari et al, 2013;Savatin et al, 2014). A recent publication by Wolf and colleagues has provided evidence that pectin in combination with brassinosteroid (BR)-based signaling processes is an important regulator of cell wall integrity (or homeostasis) during growth and development (Wolf et al, 2012b).…”
Section: Damps Pti and The Cwi Maintenance Mechanismmentioning
confidence: 99%